1997
DOI: 10.1080/026782997208578
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical phase transition behaviour of polymer azobenzene liquid crystals with flexible siloxane units as a side-chain spacer

Abstract: The in¯uence of the spacer structure on the photochemical phase transition behaviour was explored for azobenzene polymer liquid crystals (azo-PLCs) possessing siloxane spacers in the polymer side chain, and for analogue without the siloxane spacer. The photochemical phase transition of the azo-PLC with the siloxane spacer was found to proceed less e ectively than that of the azo-PLC without the siloxane spacer. It was also con® rmed that the spacer structure does not a ect the trans± cis photoisomerizatio n be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…[ 97 ] It was found that PA6AB2 underwent the nematic LC-isotropic phase transition in 200 ns upon irradiation with a laser pulse (20 ps). [ 98 ] This fast response of LCPs is an encouraging result from the viewpoint of applications in photonic devices.…”
Section: Homopolymersmentioning
confidence: 83%
See 2 more Smart Citations
“…[ 97 ] It was found that PA6AB2 underwent the nematic LC-isotropic phase transition in 200 ns upon irradiation with a laser pulse (20 ps). [ 98 ] This fast response of LCPs is an encouraging result from the viewpoint of applications in photonic devices.…”
Section: Homopolymersmentioning
confidence: 83%
“…To overcome this diffi culty, a new system has been developed, in which each mesogen in LCPs is provided with a photoresponsive moiety. [97][98][99] For instance, in AZ-containing LCPs, the AZ moiety could play both roles as a mesogen and as a photoresponsive group when it is connected with polymer main with a soft spacer. As shown in Figure 9 A, LCPs with AZ moieties in the side chain shows a very stable nematic LC phase between the glass transition temperature ( T g ) of the LCP, and the clearing point (about 150 ° C).…”
Section: Homopolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the ordered nematic phase is isothermally transformable into a disordered isotropic phase by the trans – cis photoisomerization of the guest azobenzene. The photochemical phase transition of liquid crystals has been examined by transmission and reflection mode analyses 10–14…”
Section: Introductionmentioning
confidence: 99%
“…18, 19 We have already reported several attempts to provide LCs with photoresponsive property, and have demonstrated the photonic control of light by means of the photochemical phase transition of azobenzene LCs. [20][21][22][23][24][25] Such photochemical phase transition behavior was investigated by monitoring the intensity of polarized light through a pair of crossed polarizers with the sample between them. In the previous work, we reported all-optical control of the composite films containing a conventional azobenzene ͑i.e., non donor-acceptor type azobenzene͒ as a guest molecule by the photochemical phase transition trigged by photoisomerization of the azobenzene molecule.…”
Section: Introductionmentioning
confidence: 99%